Символіка ікони як відображення та трансляція духовно-світоглядних орієнтирів людини - Ларіонова, В.; Борисевич, Л. (Інститут народознавства НАН України, 2008)
Some religious symbols possess ritual character and may serve as equivalent substitutions for holy text, deity, ethical commandments. The concept of symbolic image had been elaborated with outstanding contribution of Byzantine thinkers as Pseudo-Dionisius Areopagite, John Damascene, Theodore Studite. They had lain ground under possibility of symbolic representations of deity and saints in anthropomorphic images. The idea to raise the human spirit to higher truth being divine archetype with the help of symbolic image had become one of leading ones in Byzantine aesthetics. In the article are considered types of Lord and Virgin icons in Ukrainian sacral art. The statement is being made that icons are to be considered as means of representation and fixation of cultural and religious experience.